Coping among trauma-affected youth: a qualitative study. Issue 1 (December 2015) - Cherewick, Megan; Kohli, Anjalee; Remy, Mitima; Murhula, Clovis; Kurhorhwa, Arsene; Mirindi, Alfred; Bufole, Nadine; Banywesize, Jean; Ntakwinja, Gisele; Kindja, Gracia; Glass, Nancy
Abstract Background Eastern Democratic Republic of Congo has endured decades of conflict resulting in widespread experiences of conflict related trauma and destruction to health and social infrastructure. The aim of this qualitative study was to provide a context specific understanding of youth exposure to violence (ages 10–15 years) and use of cognitive and behavioral coping strategies. Methods A purposive sampling strategy based on age, gender and exposure to traumatic events was used to identify eligible youth in an ongoing parent study from four villages in the Walungu Territory, Eastern Democratic Republic of Congo. These four villages were selected from a total of 10 participating in the parent study because of the reported high exposure to conflict-related trauma. The interview guide consisted of broad open-ended questions related to the following topics, 1) identification of traumatic experiences, 2) methods for coping and changes in coping behavior 3) gender and age differences in coping, 4) sources of psychosocial support. A grounded theory approach was used to identify emergent themes. Results Of the 48 eligible participants identified, 30 youth completed the interview, 53 % were female (n = 16) and 47 % were male (n = 14). Youth ranged in age from 10–15 (mean age = 13.07). Exposures to different forms of violence and stress were reported among youth participants. Exposures to traumatic stressors occur at the individual, family and community level. In response to traumatic stress, youth reported both cognitive and behavioral coping strategies. Cognitive coping strategies included trying to forget and praying. Behavioral coping strategies included social support seeking and risk-taking behavior. These strategies may be used in mutually reinforcing ways, with youth employing more than one coping strategy. Conclusion This qualitative research provides important, culturally grounded information on coping strategies used by youth in rural post-conflict settings where limited psychosocial support services are available. Understanding use of cognitive and behaviors coping strategies may inform local community and international development programs to support youth mental health along adaptive trajectories resulting in promotion of well-being and reduced risk taking behaviors.